2021
DOI: 10.7554/elife.63204
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in Achilles tendon morphology and geometry changes susceptibility to injury

Abstract: The unique structure of the Achilles tendon, combining three smaller sub-tendons, enhances movement efficiency by allowing individual control from connected muscles. This requires compliant interfaces between sub-tendons, but compliance decreases with age and may account for increased injury frequency. Current understanding of sub-tendon sliding and its role in the whole Achilles tendon function is limited. Here we show changing the degree of sliding greatly affects the tendon mechanical behaviour. Our in vitr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…However, caution must be taken when interpreting these results, considering the complicated Achilles sub-tendon structure and the above-mentioned sliding mechanism. The inter-individual differences in triceps surae force distribution ( Crouzier et al, 2020 ) and the AT material properties ( Yin et al, 2021 ) need to be taken into account when targeting the “sweet spot.” All these parameters will inherently generate different internal tendon strain distribution. However, to our knowledge, there are no studies investigating strains yet, taking into account the inter-individual differences in Achilles tendinopathy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, caution must be taken when interpreting these results, considering the complicated Achilles sub-tendon structure and the above-mentioned sliding mechanism. The inter-individual differences in triceps surae force distribution ( Crouzier et al, 2020 ) and the AT material properties ( Yin et al, 2021 ) need to be taken into account when targeting the “sweet spot.” All these parameters will inherently generate different internal tendon strain distribution. However, to our knowledge, there are no studies investigating strains yet, taking into account the inter-individual differences in Achilles tendinopathy patients.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of these previous studies is that the three sub-tendons were not included in the AT models ( Hansen et al, 2017 ) or, if included, only two sub-tendons were considered (soleus and gastrocnemius) ( Shim et al, 2019 ; Handsfield et al, 2020 ). In studies that considered the three sub-tendons ( Handsfield et al, 2017 ; Knaus and Blemker, 2021 ; Yin et al, 2021 ), the focus was on the analysis of more static exercises. To compare the effect of typical exercises from rehabilitation protocols for Achilles tendinopathy, one needs to use a FE model which includes all three sub-tendons, subject-specific geometry and muscle forces.…”
Section: Introductionmentioning
confidence: 99%
“…While the sex of each donor was known, limited sample numbers means it was not possible to establish if any variability arose from sex-related differences at baseline or with ageing, as previously reported [38] . The presence of sub-tendons within the Achilles arising from the soleus and gastrocnemius muscle bellies further adds to the potential source of variation [39] . While it is possible to estimate IFM shear modulus as approximately 0.6kPa, based on average measurements from previous data, the inability to measure IFM contact area in a non-destructive manner, and subsequently accurately calculate IFM shear modulus for each sample likely increased the variability of these data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MG muscle has, on average, a higher passive shear modulus (Le Sant et al, 2017;Lindemann et al, 2020) and a larger volume (Crouzier et al, 2018) than the LG, likely providing more resistance to lengthening. Moreover, the subtendon stiffness seems to match the muscle passive stiffness with a stiffer MG subtendon compared with the LG subtendon (Yin et al, 2021). The nervous system may choose to activate the MG more than the LG to enhance the catapult-like mechanism of the stiffer MTU and larger muscle and thus to decrease the overall activation cost (Biewener and Roberts, 2000;Crouzier et al, 2018;Crowninshield and Brand, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors could explain the absence of correlations, including different tendon and muscle mechanical properties across participants. For instance, a large variability in subtendon stiffness (Yin et al, 2021) and Achilles tendon twist (Edama et al, 2015;Knaus and Blemker, 2021) has been observed between individuals. It is therefore possible that activation varies between participants to account for known differences in mechanical and architectural properties of the muscle and tendon (Aeles et al, 2017a), and enable similar movement kinetics and kinematics during motor tasks.…”
Section: Discussionmentioning
confidence: 99%